حصانة الحقيبة الدبلوماسية وأثرها على الأمن القومي الوطني في المملكة العربية السعودية - Morebah, Muhammad ibn 'Abd al-'Aziz (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This study addressed the problems of the unlawful use of diplomatic bag , and its dangerous on the national security and stability of Kingdom of Saudi Arabia , and highlighted the wrong practices in using diplomatic bag by many diplomats around the world, exploiting immunities and privileges granted to them by international diplomatic law, the study has conducted based on international diplomatic law, and touched a sensitive international legal issues of illegal use of the diplomatic bag, in the light of international diplomatic law, as well as Fiqh which is (Islamic law). The study was made clearly and expressly indicated that the illegal use of diplomatic bag is clash with international diplomatic law, as well Fiqh which is (Islamic law). Whereas, that it is necessary to the whole world to respect international diplomatic law which arranged diplomatic relations systems, such as Vienna convention on diplomatic relations which is adopted 1961. This would promote international peace, stability, and security, and would promote national security and stability of Kingdom of Saudi Arabia. In the study used several research methods, which consists the legal method based on diplomatic history, and based on the general rules of international diplomatic law which is arranging and regulating diplomatic and consular relations. In the study, it is must important and indispensable to use historic method for exploring of the existence of diplomatic and consular immunity and privileges. The heart of study has focused on the problem of the application of diplomatic and consular immunities and privileges. That is required to compile some of those problems and analysis, and to know of the causes, then to elaborate a general rules which will be govern and lead diplomatic and consular immunities and privileges, and inductive analytical approach, by reference to a several of international agreements and protocols on diplomatic relations, as well as what goes on in committees and cambers of international law, and then interpreted and analyzed, based on international diplomatic law.